2022
DOI: 10.1097/hjh.0000000000003328
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of intravenous antihypertensives on outcomes of severe hypertension in hospitalized patients without acute target organ damage

Abstract: Background: Treatment of severe inpatient hypertension (HTN) that develops during hospitalization is not informed by guidelines. Intravenous (i.v.) antihypertensives are used to manage severe HTN even in the absence of acute target organ damage; however they may result in unpredictable blood pressure (BP) reduction and cardiovascular events. Our goal was to assess the association between i.v. antihypertensives and clinical outcomes in this population. Methods: This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…31 This association between immediate BP lowering and risk for harms is consistent with our findings of greater risks of adverse outcomes among patients receiving intravenous antihypertensives and an additional observational study of intravenous antihypertensives for severely elevated BPs that found an association with increased risk for myocardial injury. 32 It remains possible that unmeasured confounders, such as requirements for nothing by mouth, could be associated with receipt of intravenous treatment and adverse outcomes. None of these studies found signals of benefit from more intensive treatment of elevated inpatient BPs; however, prospective randomized clinical trials are necessary to overcome the risk of unmeasured confounding inherent in each study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 This association between immediate BP lowering and risk for harms is consistent with our findings of greater risks of adverse outcomes among patients receiving intravenous antihypertensives and an additional observational study of intravenous antihypertensives for severely elevated BPs that found an association with increased risk for myocardial injury. 32 It remains possible that unmeasured confounders, such as requirements for nothing by mouth, could be associated with receipt of intravenous treatment and adverse outcomes. None of these studies found signals of benefit from more intensive treatment of elevated inpatient BPs; however, prospective randomized clinical trials are necessary to overcome the risk of unmeasured confounding inherent in each study.…”
Section: Discussionmentioning
confidence: 99%
“…21 For patients with asymptomatic elevated BP recordings, increased emphasis on correct measurement, confirmation of elevated BP, and evaluation for reversible factors of transient elevations may reduce the risk of overtreatment. 32 Use of intravenous antihypertensives should be discouraged. Management of elevated inpatient BP might be reenvisioned as similar to the management of inpatient sinus tachycardia, for which the focus is on treating the underlying disorder rather than routinely prescribing antiarrhythmics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have noted that the calculation of the effect estimate for i.v. antihypertensive use on acute kidney injury (AKI) and the inpatient mortality outcome was incorrect in this paper [1]. While the numerical estimates for AKI have changed, the interpretation does not (i.v.…”
mentioning
confidence: 89%